Perspective on clinical high-risk for psychosis in Africa - Awhangansi, Sewanu; Okewole, Adeniran; Archard, Philip John; O’Reilly, Michelle (Frontiers in Psychiatry, 2023)
Clinical High Risk for Psychosis has evolved in recent years as a conceptual and clinical entity, representing a shift in focus from the syndromal psychosis state to a recognition of the prepsychotic state as a period of potential preventive intervention. Much existing evidence has been generated from well-resourced countries, with a more limited body of literature available from Africa and other Majority World countries. Against a backdrop of prevailing systemic challenges, it is necessary to appraise the state of knowledge on Clinical High Risk for Psychosis in Africa. In this perspective article, we cover epidemiology, risk factors, predictors of psychosis conversion, as well as an overview of sociocultural factors, notably stigma, and the barriers to mental health services in African settings. We discuss existing and promising assessment approaches and reflect on preventive and early intervention strategies. We conclude with recommendations including the need for more clinical, longitudinal, and collaborative research anchored in an integrative transdisciplinary approach. We highlight the need for more culturally valid assessment tools and strategies to improve access to and utilization of services while also reducing stigma.